Implementasi Zoom Breakout Room sebagai Media Diskusi Kelompok dalam Pembelajaran Daring - I Made Gami Sandi Untara (Pramana: Jurnal Hasil Penelitian, 2022)
Learning that must be directed online in the midst of the Covid-19 pandemic situation has caused a lot of polemics in achieving active learning from students, especially in group discussions, so it is necessary to use materials that really help the learning process. From zoom meetings, jitsi meetings, edmudo, schoology, to the Kemendikbud and Google study houses, which include google (gmail) accounts, drives, google meet, google classroom, google forms, presentations, spreadsheets and documents. Zoom meeting online application is used to display group conversations. In this study, the authors used a literature review approach to collect textual materials and determine how best to use them. Students are given the freedom in the Zoom Breakout Room to speak in spoken language with the group to solve the challenges set by the teacher, and before the discussion begins, the teacher uses the Zoom Breakout Room to automatically determine the members of each group. In the case of Google Docs, this is used to communicate with group members so as to produce problem reports provided by the teacher in written language, as well as to demonstrate student participation in group discussions.